3‐D printed spectacles: potential, challenges and the future. (3rd February 2020) - Lee, Ling; Burnett, Anthea M; Panos, James G; Paudel, Prakash; Keys, Drew; Ansari, Harris M; Yu, Mitasha
Abstract : Three‐dimensional (3‐D) printing offers the potential to custom‐produce a wide range of manufactured objects and improve manufacturing processes. The additive manufacturing process involves material (resin, metal, ceramics or biological cells) being deposited layer upon layer, which is fused to create a 3‐D object. While 3‐D printing has been readily available in the aerospace and automotive industries, and is being used increasingly in the medical field, its potential for optometry and ophthalmic optics has rarely been discussed in depth. 3‐D printing of spectacles has the potential to provide customised experiences, to cater for those who do not fit standardised frames or for those with irregular prescriptions, and to reduce delivery times and inventory with the opportunity of increasing access to underserved populations. Here we review available 3‐D printing technologies, and the current 3‐D printed spectacle market, including testing three commercially available spectacle frames to assess compliance with ISO:12870 standards. The article then explores the challenges faced and environmental impact of implementing 3‐D printing of spectacles.